Economy ANALISIS YURIDIS TERHADAP AKAD MUSYARAKAH MUTANAQISAH DALAM PEMBIAYAAN KPR SYARIAH DAN IMPLEMENTASINYA DALAM SENGKETA EKONOMI SYARIAH: Implementasi Akad Musyarakah Mutanaqisah dalam Pembiayaan KPR Syariah dan Sengketa Ekonomi Syariah - Muhamad Dzulfikri; Micko Andira Ramadhan; R.Muhammad Ilhan Ma’ruf; Nizar Muhammad Saeful Ulum; Rizky Maulana Ardiansyah; Muhammad Zaki Alhafiz; Mahipal (PUSAT SAINS INDONESIA, 2025)
Musyarakah Mutanaqisah (MMQ) is one of the Islamic mortgage financing models that is claimed to be in accordance with the principles of cooperation and justice in Islam. However, in practice, MMQ often raises legal issues, especially in the event of debtor default and the involvement of guarantors. This study aims to examine: the legal position of the MMQ contract according to Islamic law and Indonesian positive law; and the juridical implications of the debtor's default based on PA Tangerang Decision No. 1915/Pdt.G/2024. The method used is normative juridical with statutory, conceptual, and case approaches. The results show that although MMQ is formally valid, its implementation often deviates from sharia principles, especially in terms of risk distribution and legal protection for parties who are not the main actors of the contract. Therefore, harmonization between fatwa, positive law, and technical practice is needed so that MMQ can fully reflect contractual justice.